Dispersing agent, preparation method and application thereof, negative electrode slurry, preparation method of negative electrode slurry, negative electrode plate and electrochemical device

By using sodium carboxymethylcellulose polymer as a dispersant, the chain length and the flexible chain segment are reduced, the problem of pole cracking during high-speed thick coating is solved, the energy density and efficiency of the battery are improved, and the energy density and efficiency of the battery are enhanced. The proportion of active materials has achieved higher battery performance.

CN119230831AActive Publication Date: 2024-12-31CONTEMPORARY AMPEREX TECHNOLOGY CO LTD

Patent Information

Application Number
CN202310797884.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2024-12-31
Estimated Expiration
2043-06-30

AI Technical Summary

Technical Problem

The extreme sheet is prone to cracking during high-speed thick coating, resulting in a decrease in battery energy density and efficiency.

Method used

Using sodium carboxymethylcellulose polymer as a dispersant, by reducing its chain length and increasing flexible chain segments, improves cracking problems during coating, and provides hydrogen bonding sites through hydroxyl groups to improve bonding and dispersing properties and reduces growth Use plasticizer.

Benefits of technology

It effectively reduces the cracking rate of the electrode sheet during drying, improves the energy density and efficiency of the battery, and at the same time enhances the proportion of active materials, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a dispersing agent and a preparation method and application thereof, negative electrode slurry and a preparation method thereof, a negative electrode plate and an electrochemical device. On one hand, by reducing the chain length of the sodium carboxymethyl cellulose polymer, the crystallinity of the sodium carboxymethyl cellulose polymer is reduced, the rigidity of the sodium carboxymethyl cellulose polymer is reduced, the problem of cracking of the negative electrode slurry in the high-speed thick coating process is solved, the energy density of the battery is improved, and the efficiency of the battery is improved. On the other hand, the copolymer is obtained by polymerizing unsaturated bond-containing carbon chain groups on part of hydroxyl groups of the sodium carboxymethyl cellulose polymer, so that the copolymer has a plurality of branches, and the branches provide flexible chain segments for the sodium carboxymethyl cellulose polymer and reduce the rigidity of the sodium carboxymethyl cellulose polymer; and thus, the problem of cracking of the negative electrode slurry in the high-speed thick coating process is solved, the energy density of the battery is improved, and the efficiency of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and specifically to a dispersant and a preparation method and application thereof, a negative electrode slurry and a preparation method thereof, a negative electrode sheet and an electrochemical device. Background Art

[0002] As the market demand for lithium battery energy density increases, high-speed thick coating during pole piece production is a necessary trend in subsequent battery cell design. High-speed thick coating usually refers to coating speed > 25m / min, which can increase production capacity; thick coating refers to coating weight > 180mg / 1540.25mm 2 , which can improve the battery energy density. However, high-speed thick coating has serious cracking during the drying process, causing the pole piece to warp during the drying process and further crack when passing the roller, thereby reducing the battery's energy density and efficiency. Summary of the invention

[0003] The present application is made in view of the above-mentioned problems, and its purpose is to provide a dispersant to improve the cracking problem of the negative electrode slurry during high-speed thick coating, thereby increasing the energy density of the battery and improving the efficiency of the battery.

[0004] In order to achieve the above-mentioned objectives, the embodiments of the present application provide a dispersant and a preparation method and application thereof, a negative electrode slurry and a preparation method thereof, a negative electrode sheet and an electrochemical device.

[0005] In the first aspect, the present application provides a dispersant, including a sodium carboxymethyl cellulose polymer, wherein the structural formula of the sodium carboxymethyl cellulose polymer is: including a sodium carboxymethyl cellulose polymer, wherein the structural formula of the sodium carboxymethyl cellulose polymer is:

[0006]

[0007] Wherein, R includes a group containing a carbon chain with an unsaturated bond, m is a positive integer of 1 to 10, and n is a positive integer of 1 to 100.

[0008] Thus, in the technical scheme of the embodiment of the present application, on the one hand, by reducing the chain length of the sodium carboxymethyl cellulose polymer, the crystallinity of the sodium carboxymethyl cellulose polymer is reduced, the rigidity of the sodium carboxymethyl cellulose polymer is reduced, and then the problem of cracking during the high-speed thick coating of the negative electrode slurry is improved, thereby improving the energy density of the battery and improving the efficiency of the battery. On the other hand, by polymerizing the carbon chain group containing unsaturated bonds on some hydroxyl groups of the sodium carboxymethyl cellulose polymer, a copolymer is obtained, so that the copolymer has multiple branches, and these branches provide flexible segments for the sodium carboxymethyl cellulose polymer, reduce the rigidity of the sodium carboxymethyl cellulose polymer, and then improve the problem of cracking during the high-speed thick coating of the negative electrode slurry, thereby improving the energy density of the battery and improving the efficiency of the battery. At the same time, the hydroxyl groups that are not polymerized on the sodium carboxymethyl cellulose polymer provide hydrogen bonding sites, have good bonding properties and dispersion properties, thereby reducing the use of plasticizers, and can also enhance the proportion of active materials in the negative electrode slurry, further improve the energy density of the battery, and improve the efficiency of the battery. Among them, m is a positive integer of 1 to 10, which is beneficial to reducing the crystallinity of the sodium carboxymethyl cellulose polymer. When m is greater than 10, the crystallinity of the sodium carboxymethyl cellulose polymer is still too high, and the probability of cracking during the coating process is too high. n is a positive integer of 1 to 100, which is beneficial to reducing the crystallinity of the sodium carboxymethyl cellulose polymer. When n is greater than 100, the crystallinity of the sodium carboxymethyl cellulose polymer is still too high, and the probability of cracking during the coating process is too high.

[0009] In some embodiments of the present application, the group containing an unsaturated carbon chain may be -C=C-. In some embodiments of the present application, the group containing an unsaturated carbon chain may also be -C≡C-. In some embodiments of the present application, the group containing an unsaturated carbon chain may contain both -C=C- and -C≡C-.

[0010] In any embodiment, R includes a group containing an unsaturated carbon chain with 3 to 8 carbon atoms. The group containing an unsaturated carbon chain with 3 to 8 carbon atoms can increase the flexibility of the sodium carboxymethyl cellulose polymer, reduce the crystallization performance of the sodium carboxymethyl cellulose polymer, and thus reduce the probability of cracking. When R is less than 3, the effect of increasing the flexibility of the sodium carboxymethyl cellulose polymer is limited. When R is greater than 8, the molecular chain of the group containing an unsaturated carbon chain is relatively hard, and the effect of increasing the flexibility of the sodium carboxymethyl cellulose polymer is limited. Optionally, R includes a group containing an unsaturated carbon chain with 4 to 6 carbon atoms.

[0011] In any embodiment, R also includes an oxygen-containing polar functional group, and the polar functional group containing oxygen-containing polar functional groups is conducive to coating dispersed graphite and improving the dispersion performance of sodium carboxymethyl cellulose. In some embodiments of the present application, the oxygen-containing polar functional group can be carboxylic acid, ester, amide, hydroxyl. In some embodiments of the present application, the oxygen-containing polar functional group can also be acrylic acid, acrylamide and acrylate.

[0012] In any embodiment, R includes at least one of acrylic acid, acrylamide and acrylate, which are commonly used substances in lithium battery formulations and have little effect on battery performance while also improving the flexibility of sodium carboxymethyl cellulose polymer.

[0013] In any embodiment, m is a positive integer of 4 to 8, m less than 4 affects the dispersion performance of the negative electrode active material, and m greater than 8 affects the crystallinity of the sodium carboxymethyl cellulose polymer; and / or,

[0014] n is a positive integer of 30 to 60. If n is less than 30, the dispersibility of the sodium carboxymethyl cellulose polymer will be reduced. If n is greater than 60, the flexibility of the sodium carboxymethyl cellulose polymer will be reduced and the incidence of cracking will be increased.

[0015] In the second aspect, the embodiments of the present application propose the use of the dispersant of the first aspect of the present application in negative electrode slurry.

[0016] In a third aspect, the present application embodiment provides a method for preparing the dispersant of the first aspect of the present application, comprising the following steps:

[0017] Activating the sodium carboxymethyl cellulose monomer with an activator to obtain an activated sodium carboxymethyl cellulose monomer;

[0018] The activated sodium carboxymethyl cellulose monomer is polymerized with a compound containing an unsaturated carbon chain to obtain a sodium carboxymethyl cellulose polymer.

[0019] By activating the sodium carboxymethyl cellulose monomer with an activator, part of the hydroxyl groups on the sodium carboxymethyl cellulose monomer can be formed into oxygen free radicals, which are convenient for polymerization with a compound containing an unsaturated carbon chain to obtain a sodium methyl cellulose polymer.

[0020] In any embodiment, the step is to activate the sodium carboxymethyl cellulose monomer by an activator to obtain the activated sodium carboxymethyl cellulose monomer:

[0021] The activator includes an inorganic peroxide compound. The use of an inorganic peroxide compound to activate the sodium carboxymethyl cellulose monomer can reduce the side reaction between the activator and the sodium carboxymethyl cellulose monomer while allowing some hydroxyl groups on the sodium carboxymethyl cellulose monomer to form oxygen free radicals, thereby improving the polymerization efficiency of the sodium carboxymethyl cellulose monomer and the compound containing an unsaturated carbon chain.

[0022] In any embodiment, the activator further comprises a sulfur-containing compound. The sulfur-containing compound can further cause some hydroxyl groups on the sodium carboxymethyl cellulose monomer to form oxygen free radicals, while reducing the side reaction between the activator and the sodium carboxymethyl cellulose monomer, thereby improving the efficiency of polymerization between the sodium carboxymethyl cellulose monomer and the compound containing an unsaturated carbon chain.

[0023] In any embodiment, the activator includes but is not limited to at least one of sodium bisulfite and ammonium persulfate, potassium persulfate, and sodium persulfate. By using at least one of the above activators, it is possible to further allow some of the hydroxyl groups on the sodium carboxymethylcellulose monomer to form oxygen free radicals, while reducing the side reaction between the activator and the sodium carboxymethylcellulose monomer, thereby improving the efficiency of polymerization of the sodium carboxymethylcellulose monomer with the compound containing an unsaturated carbon chain. In some embodiments of the present application, the activator may include only one of sodium bisulfite and ammonium persulfate, potassium persulfate, and sodium persulfate. In other embodiments of the present application, the activator may include two or more of sodium bisulfite and ammonium persulfate, potassium persulfate, and sodium persulfate at the same time. For example, sodium bisulfite and ammonium persulfate may be included at the same time, potassium persulfate and sodium persulfate may be included at the same time, and sodium bisulfite, ammonium persulfate, and sodium persulfate may also be included at the same time.

[0024] In any embodiment, the step is to activate the sodium carboxymethyl cellulose monomer by an activator, and the mass ratio of the activator to the sodium carboxymethyl cellulose monomer in the activated sodium carboxymethyl cellulose monomer is (1-200):100. Optionally, the mass ratio of the activator to the sodium carboxymethyl cellulose monomer is (6-80):100. The mass ratio of the activator to the sodium carboxymethyl cellulose monomer affects the formation of oxygen free radicals from some hydroxyl groups on the sodium carboxymethyl cellulose monomer. When the mass ratio of the activator to the sodium carboxymethyl cellulose monomer is less than 1:100, the oxygen free radicals formed are insufficient, thereby reducing the degree of polymerization with the compound containing an unsaturated carbon chain. When the mass ratio of the activator to the sodium carboxymethyl cellulose monomer is less than 200:100, too many hydroxyl groups form oxygen free radicals, making the degree of polymerization with the compound containing an unsaturated carbon chain too large, thereby reducing the number of hydroxyl groups, reducing the adhesion and dispersion properties of the sodium carboxymethyl cellulose, and reducing the energy density and efficiency of the battery; and / or,

[0025] The activation temperature is 50-100° C., and optionally, the activation temperature is 60-80° C. The activation temperature affects the formation of oxygen free radicals from some hydroxyl groups on the sodium carboxymethyl cellulose monomer. When the activation temperature is lower than 50° C., the rate at which the hydroxyl groups form oxygen free radicals is too slow. When the activation temperature is higher than 100° C., some activators themselves react with the sodium carboxymethyl cellulose monomer, thereby affecting the formation of oxygen free radicals. And / or,

[0026] The activation time is 3 to 8 hours, and optionally, the activation time is 4 to 6 hours. The activation time affects the formation of oxygen free radicals by some hydroxyl groups on the sodium carboxymethyl cellulose monomer. When the activation time is less than 3 hours, the oxygen free radicals formed are insufficient, thereby reducing the degree of polymerization with the compound containing an unsaturated carbon chain. When the activation time is greater than 8 hours, too many hydroxyl groups form oxygen free radicals, resulting in a large degree of polymerization with the compound containing an unsaturated carbon chain, thereby reducing the number of hydroxyl groups, reducing the adhesion and dispersion properties of the sodium carboxymethyl cellulose, and reducing the energy density and efficiency of the battery.

[0027] In any embodiment, the activated sodium carboxymethyl cellulose monomer is polymerized with a compound containing an unsaturated carbon chain to obtain a sodium carboxymethyl cellulose polymer.

[0028] The polymerization temperature is 50-80°C, and optionally, the polymerization temperature is 60-70°C. The polymerization temperature affects the polymerization degree of the sodium carboxymethyl cellulose monomer and the compound containing an unsaturated carbon chain. When the polymerization temperature is less than 50°C, the polymerization degree is too small, which reduces the proportion of the compound containing an unsaturated carbon chain in the sodium carboxymethyl cellulose polymer. When the polymerization temperature is greater than 80°C, the polymerization degree is too large, and too many compounds containing unsaturated carbon chains are in the sodium carboxymethyl cellulose polymer, thereby reducing the number of hydroxyl groups, reducing the adhesion and dispersion properties of the sodium carboxymethyl cellulose, and reducing the energy density and efficiency of the battery; and / or,

[0029] The mass ratio of activated sodium carboxymethyl cellulose monomer to the compound containing unsaturated carbon chains is 1:(1-100); optionally, the mass ratio of activated sodium carboxymethyl cellulose monomer to the compound containing unsaturated carbon chains is 1:(1-50), and the mass ratio of activated sodium carboxymethyl cellulose monomer to the compound containing unsaturated carbon chains affects the degree of polymerization of sodium carboxymethyl cellulose monomer and the compound containing unsaturated carbon chains. When the mass ratio of activated sodium carboxymethyl cellulose monomer to the compound containing unsaturated carbon chains is less than 1:100, the proportion of activated sodium carboxymethyl cellulose monomer is too small, and the proportion of compounds containing unsaturated carbon chains is too large. Too many compounds containing unsaturated carbon chains are in the sodium carboxymethyl cellulose polymer, thereby reducing the number of hydroxyl groups, reducing the adhesion and dispersion properties of sodium carboxymethyl cellulose, and reducing the energy density and efficiency of the battery. When the mass ratio of activated sodium carboxymethyl cellulose monomer to the compound containing unsaturated carbon chains is greater than 1:1, the proportion of activated sodium carboxymethyl cellulose monomer is too large, and the proportion of compounds containing unsaturated carbon chains is too small, and the improvement of the crystallinity of the sodium carboxymethyl cellulose polymer is not obvious; and / or,

[0030] The compound containing an unsaturated carbon chain includes but is not limited to at least one of acrylic acid, acrylamide and acrylate. The compound containing an unsaturated carbon chain includes but is not limited to at least one of acrylic acid, acrylamide and acrylate. The compound containing an unsaturated carbon chain can increase the degree of polymerization of the compound containing an unsaturated carbon chain and the activated sodium carboxymethyl cellulose monomer, and has good electrochemical stability. In some embodiments of the present application, the compound containing an unsaturated carbon chain may contain only any one of acrylic acid, acrylamide and acrylate. In other embodiments of the present application, the compound containing an unsaturated carbon chain may contain two or more of acrylic acid, acrylamide and acrylate at the same time.

[0031] In a fourth aspect, an embodiment of the present application proposes a negative electrode slurry, comprising a negative electrode active material, a conductive agent, a binder and the dispersant of the first aspect of the present application.

[0032] By adding a dispersant to the negative electrode slurry, the risk of cracking of the negative electrode slurry during coating can be reduced while ensuring the dispersion performance of the negative electrode active material, thereby improving the energy density and stability of the battery.

[0033] In any embodiment, the mass proportion of the dispersant in the negative electrode slurry is 0.5% to 5%, and the mass proportion of the dispersant in the negative electrode slurry affects the dispersibility of the negative electrode slurry. When the mass proportion of the dispersant in the negative electrode slurry is less than 0.5%, the dispersibility of the negative electrode slurry is poor, which affects the energy density and stability of the battery. When the mass proportion of the dispersant in the negative electrode slurry is greater than 5%, the content of the negative electrode active material is affected, thereby reducing the energy density and stability of the battery; optionally, the mass proportion of the dispersant in the negative electrode slurry is 1% to 2%.

[0034] In any embodiment, the negative electrode active material includes but is not limited to at least one of graphite, non-graphitized carbon, carbon nanomaterials, carbon-based organic metal frameworks and titanium oxides. The use of the above negative electrode active materials can reduce costs while ensuring energy density; and / or,

[0035] The conductive agent includes but is not limited to at least one of carbon nanotubes and graphene. The use of the conductive agent can reduce costs while ensuring energy density and conductive performance; and / or,

[0036] The adhesive includes but is not limited to at least one of styrene acrylic emulsion, polyvinylidene fluoride, polytetrafluoroethylene and polychlorotrifluoroethylene. The use of the above adhesive can reduce costs while ensuring bonding performance.

[0037] In a fifth aspect, the embodiment of the present application provides a method for preparing the negative electrode slurry according to the third aspect of the present application, comprising the following steps:

[0038] Adding the negative electrode active material, the conductive agent and the first part of the dispersant into the solvent and mixing to obtain a premix;

[0039] The second part of the dispersant and the binder are mixed with the premix to obtain the negative electrode slurry.

[0040] By adding the negative electrode active material, the conductive agent and the first part of the dispersant to the solvent and mixing them to obtain a premix, the negative electrode active material can be better dispersed in the solvent, and the second part of the dispersant and the binder are mixed with the premix to obtain a negative electrode slurry, and the steric hindrance of the sodium carboxymethyl cellulose polymer is utilized to make the negative electrode active material dispersed in the solvent better suspended and dispersed. In the present application, the solvent includes but is not limited to water.

[0041] In any embodiment, the mass ratio of the first part of the dispersant to the second part of the dispersant is (1-10):7. The mass ratio of the first part of the dispersant to the second part of the dispersant affects the dispersion performance and suspension performance of the negative electrode active material. When the mass ratio of the first part of the dispersant to the second part of the dispersant is less than 1:7, the dispersion performance of the negative electrode active material is poor. When the mass ratio of the first part of the dispersant to the second part of the dispersant is greater than 10:7, the suspension performance of the negative electrode active material is poor. Optionally, the mass ratio of the first part of the dispersant to the second part of the dispersant is (2-5):7.

[0042] In any embodiment, the step of adding the negative electrode active material, the conductive agent and the first part of the dispersant to the solvent to mix to obtain a premix comprises kneading, wherein:

[0043] The kneading speed is 10 to 50 rpm. The kneading speed affects the dispersion performance of the negative electrode active material. When the kneading speed is less than 10 rpm, the dispersion performance is poor. When the kneading speed is greater than 50 rpm, the negative electrode active material will be sheared, resulting in side reactions and reducing the energy density and stability of the battery. Optionally, the kneading speed is 20 to 30 rpm.

[0044] The kneading time is 10 to 120 minutes. The kneading time affects the dispersion performance of the negative electrode active material. If the kneading time is less than 10 minutes, the dispersion performance is poor. If the kneading time is greater than 120 minutes, the negative electrode active material will be sheared, resulting in side reactions and reducing the energy density and stability of the battery. Optionally, the kneading time is 60 to 90 minutes.

[0045] Through kneading, under the condition of high solid content, the mechanical force is strong and the ability to disperse the slurry is stronger. With the help of strong mechanical force, the negative electrode active material is coated, allowing the negative electrode active material to be better dispersed in the solvent.

[0046] In a sixth aspect, an embodiment of the present application provides a negative electrode sheet, comprising the negative electrode slurry of the fifth aspect of the present application.

[0047] In a seventh aspect, an embodiment of the present application provides an electrochemical device, comprising the negative electrode sheet of the sixth aspect of the present application.

[0048] In any embodiment, the electrochemical device comprises a capacitor, a primary battery, or a secondary battery. DETAILED DESCRIPTION

[0049] The following specifically discloses the embodiments of the electrolyte, the preparation method of the electrolyte, the solar power generation device, and the power-consuming device of the present application. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the following description is provided for those skilled in the art to fully understand the present application and is not intended to limit the subject matter described in the claims.

[0050] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0051] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0052] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0053] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0054] As the market demand for lithium battery energy density increases, high-speed thick coating during pole piece production is a necessary trend in subsequent battery cell design. High-speed thick coating usually refers to coating speed > 25m / min, which can increase production capacity; thick coating refers to coating weight > 180mg / 1540.25mm 2 , which can improve the battery energy density. However, high-speed thick coating has serious cracking during the drying process, causing the pole piece to warp during the drying process and further crack when passing the roller, thereby reducing the battery's energy density and efficiency.

[0055] There is serious cracking phenomenon in high-speed thick coating. The main reason is that sodium carboxymethyl cellulose will produce drying stress during the drying process, causing the electrode to warp during the drying process and further crack when passing the roller.

[0056] Therefore, there are endless technologies for studying the cracking problem of the sheet, for example, a negative electrode slurry, a negative electrode sheet, a lithium battery and an energy storage device, the negative electrode slurry includes: a negative electrode active material, a conductive agent, a binder, a dispersant and a plasticizer, wherein the plasticizer is propylene glycol and / or butylene glycol; based on the total mass of the negative electrode active material, the conductive agent, the binder and the plasticizer, the amount of propylene glycol and butylene glycol added is 0.1-0.5wt%. The role of the plasticizer increases the toughness of the negative electrode sheet to solve the coating cracking problem and improve the energy density of the electrode sheet. By adding a new auxiliary plasticizer to the anode formula, the crystallinity of sodium carboxymethyl cellulose is reduced by reducing the hydrogen bonding between sodium carboxymethyl cellulose molecules, thereby improving the molecular flexibility. However, due to the addition of new materials, the proportion of active main materials is reduced, the energy density is reduced, and the excess of plasticizer residue will cause interface problems. The plasticizer has poor compatibility with the electrolyte, so excessive residue will deteriorate the interface, further affecting the dynamics and safety issues.

[0057] Unexpectedly, a sodium carboxymethyl cellulose polymer can be obtained by free radical polymerization of some hydroxyl groups of short-chain sodium carboxymethyl cellulose with unsaturated carbon chains. The unsaturated carbon chain provides flexible segments for rigid sodium carboxymethyl cellulose, and the large number of hydroxyl groups on sodium carboxymethyl cellulose also provide hydrogen bonding sites, which have high adhesion. Using the above-synthesized flexible sodium carboxymethyl cellulose polymer as a dispersant can eliminate the addition of plasticizers, thereby solving interface problems and increasing the proportion of active materials. At the same time, it improves the energy density and stability of the battery.

[0058] Based on this, the present application provides a dispersant and a preparation method and application thereof, a negative electrode slurry and a preparation method thereof, a negative electrode sheet and an electrochemical device.

[0059] In the first aspect, the present application provides a dispersant, including a sodium carboxymethyl cellulose polymer, wherein the structural formula of the sodium carboxymethyl cellulose polymer is: including a sodium carboxymethyl cellulose polymer, wherein the structural formula of the sodium carboxymethyl cellulose polymer is:

[0060]

[0061] Wherein, R includes a group containing a carbon chain with an unsaturated bond, m is a positive integer of 1 to 10, and n is a positive integer of 1 to 100.

[0062] Thus, in the technical scheme of the embodiment of the present application, on the one hand, by reducing the chain length of the sodium carboxymethyl cellulose polymer, the crystallinity of the sodium carboxymethyl cellulose polymer is reduced, the rigidity of the sodium carboxymethyl cellulose polymer is reduced, and then the problem of cracking during the high-speed thick coating of the negative electrode slurry is improved, thereby improving the energy density of the battery and improving the efficiency of the battery. On the other hand, by polymerizing the carbon chain group containing unsaturated bonds on some hydroxyl groups of the sodium carboxymethyl cellulose polymer, a copolymer is obtained, so that the copolymer has multiple branches, and these branches provide flexible segments for the sodium carboxymethyl cellulose polymer, reduce the rigidity of the sodium carboxymethyl cellulose polymer, and then improve the problem of cracking during the high-speed thick coating of the negative electrode slurry, thereby improving the energy density of the battery and improving the efficiency of the battery. At the same time, the hydroxyl groups that are not polymerized on the sodium carboxymethyl cellulose polymer provide hydrogen bonding sites, have good bonding properties and dispersion properties, thereby reducing the use of plasticizers, and can also enhance the proportion of active materials in the negative electrode slurry, further improve the energy density of the battery, and improve the efficiency of the battery. Among them, m is a positive integer of 1 to 10, which is beneficial to reducing the crystallinity of the sodium carboxymethyl cellulose polymer. When m is greater than 10, the crystallinity of the sodium carboxymethyl cellulose polymer is still too high, and the probability of cracking during the coating process is too high. n is a positive integer of 1 to 100, which is beneficial to reducing the crystallinity of the sodium carboxymethyl cellulose polymer. When n is greater than 100, the crystallinity of the sodium carboxymethyl cellulose polymer is still too high, and the probability of cracking during the coating process is too high.

[0063] In some embodiments of the present application, the group containing an unsaturated carbon chain may be -C=C-. In some embodiments of the present application, the group containing an unsaturated carbon chain may also be -C≡C-. In some embodiments of the present application, the group containing an unsaturated carbon chain may contain both -C=C- and -C≡C-.

[0064] In any embodiment, R includes a group of carbon chains containing unsaturated bonds of 3 to 8 carbon atoms. The group of carbon chains containing unsaturated bonds of 3 to 8 carbon atoms can increase the flexibility of the sodium carboxymethyl cellulose polymer, reduce the crystallization properties of the sodium carboxymethyl cellulose polymer, and thus reduce the probability of cracking. When R is less than 3, the effect of increasing the flexibility of the sodium carboxymethyl cellulose polymer is limited. When R is greater than 8, the molecular chain of the group containing unsaturated bonds is relatively hard, and the effect of increasing the flexibility of the sodium carboxymethyl cellulose polymer is limited. R can be a group of carbon chains containing unsaturated bonds of 3, 4, 5, 6, 7 or 8 carbon atoms. Optionally, R includes a group of carbon chains containing unsaturated bonds of 4 to 6 carbon atoms.

[0065] In any embodiment, R also includes an oxygen-containing polar functional group, and the polar functional group containing oxygen-containing polar functional groups is conducive to coating dispersed graphite and improving the dispersion performance of sodium carboxymethyl cellulose. In some embodiments of the present application, the oxygen-containing polar functional group can be carboxylic acid, ester, amide, hydroxyl. In some embodiments of the present application, the oxygen-containing polar functional group can also be acrylic acid, acrylamide and acrylate.

[0066] In any embodiment, R includes at least one of acrylic acid, acrylamide and acrylate, which are commonly used substances in lithium battery formulations and have little effect on battery performance while also improving the flexibility of sodium carboxymethyl cellulose polymer.

[0067] In any embodiment, m is a positive integer of 4 to 8, m less than 4 affects the dispersion performance of the negative electrode active material, m greater than 8 affects the crystallinity of the sodium carboxymethyl cellulose polymer, and the value of m can be 4, 5, 6, 7, or 8; and / or,

[0068] n is a positive integer of 30 to 60. If n is less than 30, the dispersion performance of the sodium carboxymethyl cellulose polymer will be reduced. If n is greater than 60, the flexibility of the sodium carboxymethyl cellulose polymer will be reduced and the incidence of cracking will be increased. The value of n can be 30, 35, 40, 45, 50, 55 or 60, or any positive integer between 30 and 60.

[0069] In the second aspect, the embodiments of the present application propose the use of the dispersant of the first aspect of the present application in negative electrode slurry.

[0070] In a third aspect, the present application embodiment provides a method for preparing the dispersant of the first aspect of the present application, comprising the following steps:

[0071] Activating the sodium carboxymethyl cellulose monomer with an activator to obtain an activated sodium carboxymethyl cellulose monomer;

[0072] The activated sodium carboxymethyl cellulose monomer is polymerized with a compound containing an unsaturated carbon chain to obtain a sodium carboxymethyl cellulose polymer.

[0073] By activating the sodium carboxymethyl cellulose monomer with an activator, part of the hydroxyl groups on the sodium carboxymethyl cellulose monomer can be formed into oxygen free radicals, which are convenient for polymerization with a compound containing an unsaturated carbon chain to obtain a sodium methyl cellulose polymer.

[0074] In any embodiment, the step is to activate the sodium carboxymethyl cellulose monomer by an activator to obtain the activated sodium carboxymethyl cellulose monomer:

[0075] The activator includes an inorganic peroxide compound. The use of an inorganic peroxide compound to activate the sodium carboxymethyl cellulose monomer can reduce the side reaction between the activator and the sodium carboxymethyl cellulose monomer while allowing some hydroxyl groups on the sodium carboxymethyl cellulose monomer to form oxygen free radicals, thereby improving the polymerization efficiency of the sodium carboxymethyl cellulose monomer and the compound containing an unsaturated carbon chain.

[0076] In any embodiment, the activator further comprises a sulfur-containing compound. The sulfur-containing compound can further cause some hydroxyl groups on the sodium carboxymethyl cellulose monomer to form oxygen free radicals, while reducing the side reaction between the activator and the sodium carboxymethyl cellulose monomer, thereby improving the efficiency of polymerization between the sodium carboxymethyl cellulose monomer and the compound containing an unsaturated carbon chain.

[0077] In any embodiment, the activator includes but is not limited to at least one of sodium bisulfite and ammonium persulfate, potassium persulfate, and sodium persulfate. By using at least one of the above activators, it is possible to further allow some of the hydroxyl groups on the sodium carboxymethylcellulose monomer to form oxygen free radicals, while reducing the side reaction between the activator and the sodium carboxymethylcellulose monomer, thereby improving the efficiency of polymerization of the sodium carboxymethylcellulose monomer with the compound containing an unsaturated carbon chain. In some embodiments of the present application, the activator may include only one of sodium bisulfite and ammonium persulfate, potassium persulfate, and sodium persulfate. In other embodiments of the present application, the activator may include two or more of sodium bisulfite and ammonium persulfate, potassium persulfate, and sodium persulfate at the same time. For example, sodium bisulfite and ammonium persulfate may be included at the same time, potassium persulfate and sodium persulfate may be included at the same time, and sodium bisulfite, ammonium persulfate, and sodium persulfate may also be included at the same time.

[0078] In any embodiment, the step is to activate the sodium carboxymethyl cellulose monomer by an activator, and the mass ratio of the activator to the sodium carboxymethyl cellulose monomer in the activated sodium carboxymethyl cellulose monomer is (1-200):100. Optionally, the mass ratio of the activator to the sodium carboxymethyl cellulose monomer is (6-80):100. The mass ratio of the activator to the sodium carboxymethyl cellulose monomer affects the formation of oxygen free radicals by part of the hydroxyl groups on the sodium carboxymethyl cellulose monomer. When the mass ratio of the activator to the sodium carboxymethyl cellulose monomer is less than 1:100, the oxygen free radicals formed are insufficient, which reduces the polymerization of the compound containing an unsaturated carbon chain. When the mass ratio of the activator to the sodium carboxymethyl cellulose monomer is less than 200:100, too many hydroxyl groups form oxygen free radicals, so that the degree of polymerization with the compound containing an unsaturated carbon chain is too large, thereby reducing the number of hydroxyl groups, reducing the adhesion and dispersion properties of the sodium carboxymethyl cellulose, and reducing the energy density and efficiency of the battery. The mass ratio of the activator to the sodium carboxymethyl cellulose monomer can be 1:100, 1:80, 1:50, 1:10, 1:5, 1:4, 1:3, 1:2, 1:1 or 2:1, or any value between (1 and 200):100; and / or,

[0079] The activation temperature is 50-100°C. The activation temperature affects the formation of oxygen free radicals from some hydroxyl groups on the sodium carboxymethyl cellulose monomer. When the activation temperature is lower than 50°C, the rate at which the hydroxyl groups form oxygen free radicals is too slow. When the activation temperature is higher than 100°C, some activators themselves react with the sodium carboxymethyl cellulose monomer, thereby affecting the formation of oxygen free radicals. The activation temperature can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C or 100°C. Optionally, the activation temperature is 60-80°C; and / or,

[0080] The activation time is 3 to 8 hours. The activation time affects the formation of oxygen free radicals by some hydroxyl groups on the sodium carboxymethyl cellulose monomer. When the activation time is less than 3 hours, the oxygen free radicals formed are insufficient, which reduces the degree of polymerization with the compound containing unsaturated carbon chains. When the activation time is greater than 8 hours, too many hydroxyl groups form oxygen free radicals, which makes the degree of polymerization with the compound containing unsaturated carbon chains too large, thereby reducing the number of hydroxyl groups, reducing the adhesion and dispersion properties of sodium carboxymethyl cellulose, and reducing the energy density and efficiency of the battery. The activation time can be 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours or 8 hours. Optionally, the activation time is 4 to 6 hours.

[0081] In any embodiment, the activated sodium carboxymethyl cellulose monomer is polymerized with a compound containing an unsaturated carbon chain to obtain a sodium carboxymethyl cellulose polymer.

[0082] The polymerization temperature is 50-80°C. The polymerization temperature affects the polymerization degree of the sodium carboxymethyl cellulose monomer and the compound containing an unsaturated carbon chain. When the polymerization temperature is less than 50°C, the polymerization degree is too small, which reduces the proportion of the compound containing an unsaturated carbon chain in the sodium carboxymethyl cellulose polymer. When the polymerization temperature is greater than 80°C, the polymerization degree is too large, and too many compounds containing unsaturated carbon chains are in the sodium carboxymethyl cellulose polymer, thereby reducing the number of hydroxyl groups, reducing the adhesion and dispersibility of the sodium carboxymethyl cellulose, and reducing the energy density and efficiency of the battery. The polymerization temperature can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C. Optionally, the polymerization temperature is 60-70°C; and / or,

[0083] The mass ratio of the activated sodium carboxymethyl cellulose monomer to the compound containing an unsaturated carbon chain is 1:(1-100). The mass ratio of the activated sodium carboxymethyl cellulose monomer to the compound containing an unsaturated carbon chain affects the polymerization degree of the sodium carboxymethyl cellulose monomer and the compound containing an unsaturated carbon chain. When the mass ratio of the activated sodium carboxymethyl cellulose monomer to the compound containing an unsaturated carbon chain is less than 1:100, the proportion of the activated sodium carboxymethyl cellulose monomer is too small, and the proportion of the compound containing an unsaturated carbon chain is too large. Too many compounds containing unsaturated carbon chains are in the sodium carboxymethyl cellulose polymer, thereby reducing the number of hydroxyl groups, reducing the adhesion and dispersion properties of the sodium carboxymethyl cellulose, and reducing the energy density and efficiency of the battery. When the mass ratio of the activated sodium carboxymethyl cellulose monomer to the compound containing an unsaturated carbon chain is greater than 1:1, the proportion of the activated sodium carboxymethyl cellulose monomer is too large, and the proportion of the compound containing an unsaturated carbon chain is too small, and the crystallinity of the sodium carboxymethyl cellulose polymer is not significantly improved. The mass ratio of the activated sodium carboxymethyl cellulose monomer to the compound containing an unsaturated carbon chain can be 1:1, 1:5, 1:10, 1:15, 1:20, 1:25, 1:30, 1:35, 1:40, 1:45, 1:50, 1:60, 1:70, 1:80, 1:90 or 1:100, or any value between 1:(1 and 100); optionally, the mass ratio of the activated sodium carboxymethyl cellulose monomer to the compound containing an unsaturated carbon chain is 1:(1 to 50); and / or,

[0084] The compound containing an unsaturated carbon chain includes but is not limited to at least one of acrylic acid, acrylamide and acrylate. The compound containing an unsaturated carbon chain includes but is not limited to at least one of acrylic acid, acrylamide and acrylate. The compound containing an unsaturated carbon chain can increase the degree of polymerization of the compound containing an unsaturated carbon chain and the activated sodium carboxymethyl cellulose monomer, and has good electrochemical stability. In some embodiments of the present application, the compound containing an unsaturated carbon chain may contain only any one of acrylic acid, acrylamide and acrylate. In other embodiments of the present application, the compound containing an unsaturated carbon chain may contain two or more of acrylic acid, acrylamide and acrylate at the same time.

[0085] In a fourth aspect, an embodiment of the present application proposes a negative electrode slurry, comprising a negative electrode active material, a conductive agent, a binder and the dispersant of the first aspect of the present application.

[0086] By adding a dispersant to the negative electrode slurry, the risk of cracking of the negative electrode slurry during coating can be reduced while ensuring the dispersion performance of the negative electrode active material, thereby improving the energy density and stability of the battery.

[0087] In any embodiment, the mass proportion of the dispersant in the negative electrode slurry is 0.5% to 5%, and the mass proportion of the dispersant in the negative electrode slurry affects the dispersibility of the negative electrode slurry. When the mass proportion of the dispersant in the negative electrode slurry is less than 0.5%, the dispersibility of the negative electrode slurry is poor, which affects the energy density and stability of the battery. When the mass proportion of the dispersant in the negative electrode slurry is greater than 5%, the content of the negative electrode active material is affected, thereby reducing the energy density and stability of the battery. The mass proportion of the dispersant in the negative electrode slurry can be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%, or it can be any value between 0.5% and 5%; optionally, the mass proportion of the dispersant in the negative electrode slurry is 1% to 2%.

[0088] In any embodiment, the negative electrode active material includes but is not limited to at least one of graphite, non-graphitized carbon, carbon nanomaterials, carbon-based organic metal frameworks and titanium oxides. The use of the above negative electrode active materials can reduce costs while ensuring energy density; and / or,

[0089] The conductive agent includes but is not limited to at least one of carbon nanotubes and graphene. The use of the conductive agent can reduce costs while ensuring energy density and conductive performance; and / or,

[0090] The adhesive includes but is not limited to at least one of styrene acrylic emulsion, polyvinylidene fluoride, polytetrafluoroethylene and polychlorotrifluoroethylene. The use of the above adhesive can reduce costs while ensuring bonding performance.

[0091] In a fifth aspect, the embodiment of the present application provides a method for preparing the negative electrode slurry according to the third aspect of the present application, comprising the following steps:

[0092] Adding the negative electrode active material, the conductive agent and the first part of the dispersant into the solvent and mixing to obtain a premix;

[0093] The second part of the dispersant and the binder are mixed with the premix to obtain the negative electrode slurry.

[0094] By adding the negative electrode active material, the conductive agent and the first part of the dispersant to the solvent and mixing them to obtain a premix, the negative electrode active material can be better dispersed in the solvent, and the second part of the dispersant and the binder are mixed with the premix to obtain a negative electrode slurry, and the steric hindrance of the sodium carboxymethyl cellulose polymer is utilized to make the negative electrode active material dispersed in the solvent better suspended and dispersed. In the present application, the solvent includes but is not limited to water.

[0095] In any embodiment, the mass ratio of the first part of the dispersant to the second part of the dispersant is (1-10):7. The mass ratio of the first part of the dispersant to the second part of the dispersant affects the dispersion performance and suspension performance of the negative electrode active material. When the mass ratio of the first part of the dispersant to the second part of the dispersant is less than 1:7, the dispersion performance of the negative electrode active material is poor. When the mass ratio of the first part of the dispersant to the second part of the dispersant is greater than 10:7, the suspension performance of the negative electrode active material is poor. The mass ratio of the first part of the dispersant to the second part of the dispersant can be 1:7, 2:7, 3:7, 4:7, 5:7, 6:7, 1:1, 8:7, 9:7 or 10:7, or it can be any value between (1-10):7; optionally, the mass ratio of the first part of the dispersant to the second part of the dispersant is (2-5):7.

[0096] In any embodiment, the step of adding the negative electrode active material, the conductive agent and the first part of the dispersant to the solvent to mix to obtain a premix comprises kneading, wherein:

[0097] The kneading speed is 10 to 50 rpm. The kneading speed affects the dispersion performance of the negative electrode active material. When the kneading speed is less than 10 rpm, the dispersion performance is poor. When the kneading speed is greater than 50 rpm, the negative electrode active material will be sheared, resulting in side reactions and reducing the energy density and stability of the battery. Optionally, the kneading speed is 20 to 30 rpm.

[0098] The kneading time is 10 to 120 minutes. The kneading time affects the dispersion performance of the negative electrode active material. If the kneading time is less than 10 minutes, the dispersion performance is poor. If the kneading time is greater than 120 minutes, the negative electrode active material will be sheared, resulting in side reactions and reducing the energy density and stability of the battery. Optionally, the kneading time is 60 to 90 minutes.

[0099] Through kneading, under the condition of high solid content, the mechanical force is strong and the ability to disperse the slurry is stronger. With the help of strong mechanical force, the negative electrode active material is coated, allowing the negative electrode active material to be better dispersed in the solvent.

[0100] In a sixth aspect, an embodiment of the present application provides a negative electrode sheet, comprising the negative electrode slurry of the fifth aspect of the present application.

[0101] In a seventh aspect, an embodiment of the present application provides an electrochemical device, comprising the negative electrode sheet of the sixth aspect of the present application.

[0102] In any embodiment, the electrochemical device comprises a capacitor, a primary battery, or a secondary battery.

[0103] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention, and are not used to limit the present invention.

[0104] Example

[0105] The dispersants of Examples 1 to 17 of the present application have parameters according to Table 1, and the parameters of the negative electrode slurries of Examples 18 to 40 and the negative electrode slurries of Comparative Examples 1 to 8 have parameters according to Table 2.

[0106] Table 1 Parameters of dispersants of Examples 1 to 17

[0107] Dispersants Sodium carboxymethyl cellulose polymer Example 1 R=2,m=6,n=50,oxygen-containing polar functional group Example 2 R=2, m=1, n=100, oxygen-containing polar functional group Example 3 R=3, m=10, n=1, oxygen-containing polar functional group Example 4 R=10, m=6, n=50, oxygen-containing polar functional group Example 5 R=3,m=6,n=50,oxygen-containing polar functional group Example 6 R=4,m=6,n=50,oxygen-containing polar functional group Example 7 R=4,m=6,n=50,no oxygen polar functional group Example 8 R=6,m=6,n=50,oxygen-containing polar functional group Example 9 R=8,m=6,n=50,oxygen-containing polar functional group Example 10 R=5,m=4,n=30,oxygen-containing polar functional group Embodiment 11 R=5,m=8,n=40,oxygen-containing polar functional group Example 12 R=5,m=4,n=60,oxygen-containing polar functional group Embodiment 13 R is acrylic acid, m=7, n=55 Embodiment 14 R is acrylamide, m=7, n=55 Embodiment 15 R is acrylate, m=7, n=55 Example 16 R is acrylic acid or acrylamide, m=7, n=55 Embodiment 17 R is acrylic acid, acrylamide, acrylate, m=7, n=55

[0108] Table 2 Parameters of negative electrode slurries of Examples 18 to 40 and negative electrode slurries of Comparative Examples 1 to 7

[0109]

[0110]

[0111] Embodiment 41

[0112] A method for preparing a dispersant comprises the following steps:

[0113] Activating the sodium carboxymethyl cellulose monomer with an activator to obtain an activated sodium carboxymethyl cellulose monomer;

[0114] The activated sodium carboxymethyl cellulose monomer is polymerized with a compound containing an unsaturated carbon chain to obtain a sodium carboxymethyl cellulose polymer.

[0115] Embodiment 42

[0116] A method for preparing a dispersant comprises the following steps:

[0117] Activating the sodium carboxymethyl cellulose monomer with an inorganic peroxide compound to obtain an activated sodium carboxymethyl cellulose monomer;

[0118] The activated sodium carboxymethyl cellulose monomer is polymerized with a compound containing an unsaturated carbon chain to obtain a sodium carboxymethyl cellulose polymer.

[0119] Embodiment 43

[0120] A method for preparing a dispersant comprises the following steps:

[0121] The sodium carboxymethyl cellulose monomer is activated by ammonium sulfate and potassium persulfate at the same time to obtain an activated sodium carboxymethyl cellulose monomer, wherein the mass ratio of the activator to the sodium carboxymethyl cellulose monomer is 50:100, the activation temperature is 65° C., and the activation time is 5 hours;

[0122] The activated sodium carboxymethyl cellulose monomer is polymerized with acrylic acid to obtain a sodium carboxymethyl cellulose polymer, wherein the polymerization reaction temperature is 65° C., and the mass ratio of the activated sodium carboxymethyl cellulose monomer to the compound containing an unsaturated carbon chain is 1:2.

[0123] Embodiment 44

[0124] A method for preparing a negative electrode slurry comprises the following steps:

[0125] Adding the negative electrode active material, the conductive agent and the first part of the dispersant into the solvent and mixing to obtain a premix;

[0126] The second part of the dispersant and the binder are mixed with the premix to obtain the negative electrode slurry.

[0127] Embodiment 45

[0128] A method for preparing a negative electrode slurry comprises the following steps:

[0129] Adding graphite, carbon nanotubes and the first part of the carboxymethyl cellulose sodium polymer with R=8, m=6, n=50 and oxygen-containing polar functional groups into the dissolved water and mixing to obtain a premix;

[0130] The second part of the carboxymethyl cellulose sodium polymer with R=8, m=6, n=50 and oxygen-containing polar functional groups and polyvinylidene fluoride are mixed with the premix to obtain a negative electrode slurry, wherein the mass ratio of the first part of the dispersant to the second part of the dispersant is 3:7.

[0131] Embodiment 46

[0132] A method for preparing a negative electrode slurry comprises the following steps:

[0133] Add graphite, carbon nanotubes and the first part of carboxymethyl cellulose sodium polymer with R=8, m=6, n=50 and oxygen-containing polar functional groups into water, and knead at 25 rpm for 75 minutes to obtain a premix;

[0134] The second part of the carboxymethyl cellulose sodium polymer with R=8, m=6, n=50 and oxygen-containing polar functional groups and polyvinylidene fluoride are mixed with the premix to obtain a negative electrode slurry, wherein the mass ratio of the first part of the dispersant to the second part of the dispersant is 3:7.

[0135] Performance Testing

[0136] 1. Slurry filterability test

[0137] The negative electrode slurries of Examples 14 to 32 and Comparative Examples 1 to 8 were filtered under a filter screen with a 150-mesh size and a size of 25 cm*25 cm folded into a triangle. 500 mL of the slurry was poured into the filter screen. The slurry began to flow out from the tip of the filter screen. The slurry filtration time was recorded. The results are shown in Table 3.

[0138] 2. Observe the gelation and sedimentation state of the slurry

[0139] The negative electrode slurries of Examples 14 to 32 and Comparative Examples 1 to 8 were placed for different periods of time to observe whether the slurries appeared in a jelly gel state, and the slurry viscosity was tested. If the viscosity of the upper slurry in the test beaker decreased and the lower slurry thickened, it indicated that the slurry sedimentation occurred. The results are shown in Table 3.

[0140] 3. Observe the slurry coating window

[0141] The negative electrode slurries of Examples 14 to 32 and Comparative Examples 1 to 8 were coated, and the cracking of the electrode sheets was observed. The maximum coating weight without cracking was measured. The results are shown in Table 3.

[0142] 4. Battery DC impedance performance

[0143] At 25°C, the negative electrode slurries of Examples 14 to 32 and Comparative Examples 1 to 8 were prepared into batteries, respectively, and charged to 4.2V at a constant current of 1 / 3C, and then charged to a current of 0.05C at a constant voltage of 4.2V, and after standing for 5 minutes, the voltage V1 was recorded. Then, the battery was discharged at 1 / 3C for 30 seconds, and the voltage V2 was recorded. Then, the internal resistance DCR of the battery was obtained by (V2-V1) / 1 / 3C, and the results are shown in Table 3.

[0144] 5. Battery efficiency

[0145] The test process is as follows: at 25°C, the battery corresponding to Example 1 is charged to 4.3V at a constant current of 1 / 3*C, then charged to a current of 0.05C at a constant voltage of 4.3V, left for 5 minutes, and then discharged to 2.8V at 1 / 3C. The obtained capacity is recorded as the initial capacity C0. Repeat the above steps for the same battery, but change the charge and discharge rate to 4C, and cycle 10 times; then cycle the same battery again at 0.33C for 1000 cycles, and record the capacity C after 1000 cycles. 1000 , the cycle capacity retention rate is C 1000 / C0, the larger this value is, the better the cycle performance and battery efficiency is.

[0146] Table 3 Properties of negative electrode slurries of Examples 14 to 32 and Comparative Examples 1 to 8

[0147]

[0148]

[0149] It can be seen from Examples 18 to 40 and Comparative Examples 1 to 8 that, on the one hand, by reducing the chain length of the sodium carboxymethyl cellulose polymer, the crystallinity of the sodium carboxymethyl cellulose polymer is reduced, the rigidity of the sodium carboxymethyl cellulose polymer is reduced, and the problem of cracking during the high-speed thick coating of the negative electrode slurry is improved, thereby improving the energy density of the battery and improving the efficiency of the battery. On the other hand, by polymerizing the carbon chain group containing an unsaturated bond on some hydroxyl groups of the sodium carboxymethyl cellulose polymer, a copolymer is obtained, so that the copolymer has multiple branches, and these branches provide flexible segments for the sodium carboxymethyl cellulose polymer, reduce the rigidity of the sodium carboxymethyl cellulose polymer, and then improve the problem of cracking during the high-speed thick coating of the negative electrode slurry, thereby improving the energy density of the battery and improving the efficiency of the battery. At the same time, the hydroxyl groups that are not polymerized on the sodium carboxymethyl cellulose polymer provide hydrogen bonding sites, and have good bonding and dispersion properties, so that the use of plasticizers can be reduced, and the proportion of active materials in the negative electrode slurry can be increased, further improving the energy density of the battery and improving the efficiency of the battery. m is a positive integer of 1 to 10, which is beneficial to reducing the crystallinity of the sodium carboxymethyl cellulose polymer. When m is greater than 10, the crystallinity of the sodium carboxymethyl cellulose polymer is still too high, and the probability of cracking during the coating process is too high. n is a positive integer of 1 to 100, which is beneficial to reducing the crystallinity of the sodium carboxymethyl cellulose polymer. When n is greater than 100, the crystallinity of the sodium carboxymethyl cellulose polymer is still too high, and the probability of cracking during the coating process is too high.

[0150] It can be seen from Comparative Examples 1 to 8 that when m is greater than 10, the crystallinity of the sodium carboxymethyl cellulose polymer is still too high, and the probability of cracking during the coating process is too high. When m is 0, the softening effect is not good. When n is greater than 100, the crystallinity of the sodium carboxymethyl cellulose polymer is still too high, and the probability of cracking during the coating process is too high. When n is 0, the dispersion effect is too poor.

[0151] It can be seen from Examples 35 to 40 that the mass proportion of the dispersant in the negative electrode slurry affects the dispersion performance of the negative electrode slurry. When the mass proportion of the dispersant in the negative electrode slurry is less than 0.5%, the dispersion performance of the negative electrode slurry is poor, which affects the energy density and stability of the battery. When the mass proportion of the dispersant in the negative electrode slurry is greater than 5%, it affects the content of the negative electrode active material, thereby reducing the energy density and stability of the battery.

[0152] In summary, the dispersant proposed in this application, on the one hand, reduces the crystallinity of the sodium carboxymethyl cellulose polymer by reducing the chain length of the sodium carboxymethyl cellulose polymer, reduces the rigidity of the sodium carboxymethyl cellulose polymer, and then improves the problem of cracking during the high-speed thick coating of the negative electrode slurry, thereby improving the efficiency of the battery. On the other hand, by polymerizing the carbon chain group containing an unsaturated bond on some hydroxyl groups of the sodium carboxymethyl cellulose polymer, a copolymer is obtained, so that the copolymer has multiple branches, and these branches provide flexible segments for the sodium carboxymethyl cellulose polymer, reduce the rigidity of the sodium carboxymethyl cellulose polymer, and then improve the problem of cracking during the high-speed thick coating of the negative electrode slurry, thereby improving the energy density of the battery and improving the efficiency of the battery. At the same time, the hydroxyl groups that are not polymerized on the sodium carboxymethyl cellulose polymer provide hydrogen bonding sites, have good bonding properties and dispersion properties, thereby reducing the use of plasticizers, and can also increase the proportion of active materials in the negative electrode slurry, further improve the energy density of the battery, and improve the efficiency of the battery. When m is greater than 10, the crystallinity of the sodium carboxymethyl cellulose polymer is still too high, and the probability of cracking during coating is too high. When n is greater than 100, the crystallinity of the sodium carboxymethyl cellulose polymer is still too high, and the probability of cracking during coating is too high.

[0153] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.

Claims

1. A dispersant for negative electrode slurry, characterized in that: It includes a sodium carboxymethyl cellulose polymer, and the structural formula of the sodium carboxymethyl cellulose polymer is: Wherein, R includes a group containing a carbon chain with an unsaturated bond, m is a positive integer of 1 to 10, and n is a positive integer of 1 to 100.

2. The dispersant according to claim 1, characterized in that R includes a group of a carbon chain containing unsaturated bonds of 3 to 8 carbon atoms; alternatively, R includes a group of a carbon chain containing unsaturated bonds of 4 to 6 carbon atoms.

3. The dispersant according to claim 1 or 2, characterized in that R also includes oxygen-containing polar functional groups.

4. The dispersant according to any one of claims 1 to 3, characterized in that R includes at least one of acrylic acid, acrylamide and acrylate.

5. The dispersant according to any one of claims 1 to 4, characterized in that m is a positive integer from 4 to 8; and / or, n is a positive integer ranging from 30 to 60.

6. Use of the dispersant according to any one of claims 1 to 5 in negative electrode slurry.

7. The method for preparing a dispersant according to any one of claims 1 to 5, characterized in that: The following steps are involved: Activating the sodium carboxymethyl cellulose monomer with an activator to obtain an activated sodium carboxymethyl cellulose monomer; The activated sodium carboxymethyl cellulose monomer is polymerized with a compound containing an unsaturated carbon chain to obtain a sodium carboxymethyl cellulose polymer.

8. The method for preparing a dispersant according to claim 7, characterized in that: Step: Activate the sodium carboxymethyl cellulose monomer with an activator to obtain the activated sodium carboxymethyl cellulose monomer: Activators include inorganic peroxygen compounds.

9. The method for preparing a dispersant according to claim 8, characterized in that: Activators also include sulfur-containing compounds.

10. The method for preparing a dispersant according to claim 8 or 9, characterized in that: The activator includes sodium bisulfite and at least one of ammonium persulfate, potassium persulfate and sodium persulfate.

11. The method for preparing a dispersant according to any one of claims 7 to 10, characterized in that: Step: activating the sodium carboxymethyl cellulose monomer by an activator to obtain an activated sodium carboxymethyl cellulose monomer. The mass ratio of the activator to the sodium carboxymethyl cellulose monomer is (1-200):100, optionally, the mass ratio of the activator to the sodium carboxymethyl cellulose monomer is (6-80):100; and / or, The activation temperature is 50-100°C, optionally, the activation temperature is 60-80°C; and / or, The activation time is 3 to 8 hours, and optionally, the activation time is 4 to 6 hours.

12. The method for preparing a dispersant according to any one of claims 7 to 11, characterized in that: Step 1: polymerizing the activated sodium carboxymethyl cellulose monomer with the compound containing an unsaturated carbon chain to obtain a sodium carboxymethyl cellulose polymer. The polymerization temperature is 50-80°C, optionally, the polymerization temperature is 60-70°C; and / or, The mass ratio of the activated sodium carboxymethyl cellulose monomer to the compound containing an unsaturated carbon chain is 1:(1-100); optionally, the mass ratio of the activated sodium carboxymethyl cellulose monomer to the compound containing an unsaturated carbon chain is 1:(1-50); and / or, The compound containing an unsaturated carbon chain includes at least one of acrylic acid, acrylamide and acrylate.

13. A negative electrode slurry, characterized in that: The invention comprises a negative electrode active material, a conductive agent, a binder and a dispersant as claimed in any one of claims 1 to 5.

14. The negative electrode slurry according to claim 13, characterized in that: The mass proportion of the dispersant in the negative electrode slurry is 0.5% to 5%; optionally, the mass proportion of the dispersant in the negative electrode slurry is 1% to 2%.

15. The negative electrode slurry according to claim 13 or 14, characterized in that: The negative electrode active material comprises at least one of graphite, non-graphitizable carbon, carbon nanomaterials, carbon-based organic metal frameworks and titanium oxides; and / or, The conductive agent includes at least one of carbon nanotubes and graphene; and / or, The binder includes at least one of styrene acrylic emulsion, polyvinylidene fluoride, polytetrafluoroethylene and polychlorotrifluoroethylene.

16. A method for preparing a negative electrode slurry according to any one of claims 13 to 15, characterized in that: The following steps are involved: Adding the negative electrode active material, the conductive agent and the first part of the dispersant into the solvent and mixing to obtain a premix; The second part of the dispersant and the binder are mixed with the premix to obtain the negative electrode slurry.

17. The method for preparing negative electrode slurry according to claim 16, characterized in that: The mass ratio of the first part of the dispersant to the second part of the dispersant is (1-10):7; optionally, the mass ratio of the first part of the dispersant to the second part of the dispersant is (2-5):

7.

18. The method for preparing negative electrode slurry according to claim 16 or 17, characterized in that: Step A negative electrode active material, a conductive agent and a first portion of a dispersant are added to a solvent and mixed to obtain a premix, wherein the mixing method includes kneading, wherein: The kneading rotation speed is 10 to 50 rpm, and optionally, the kneading rotation speed is 20 to 30 rpm. The kneading time is 10 to 120 minutes, and optionally, the kneading time is 60 to 90 minutes.

19. A negative electrode sheet, characterized in that: The invention comprises a negative electrode slurry prepared by the negative electrode slurry according to any one of claims 13 to 15 or the negative electrode slurry preparation method according to any one of claims 16 to 18.

20. An electrochemical device, characterized in that: Comprising the negative electrode sheet as claimed in claim 19.

21. The electrochemical device according to claim 20, characterized in that The electrochemical device includes a capacitor, a primary battery, or a secondary battery.

Citation Information

Patent Citations

  • Lithium ion battery cathode and lithium ion battery therewith

    CN102368543A

  • Negative electrode for rechargeable lithium battery and rechargeable lithium battery including same

    CN105098190A

  • Lithium ion battery negative electrode slurry and preparation method thereof, lithium ion battery negative electrode plate and lithium ion battery

    CN116014135A

  • Carboxymethyl cellulose copolymer binder as well as preparation method and application thereof

    CN116023881A

  • Negative electrode for lithium secondary battery

    JP2004087227A

Cited By

  • Carbon nanomaterial dispersions and methods for preparation thereof

    WO2026209428A1